POLIGAMI DALAM TEORI HERMENEUTIKA MUHAMMAD SHAHRÃ»R - Tamu, Yowan (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
Muhammad Shah}rûr was a liberal philosopher from Suriah. Most scholars who study Shahrûr?s thought split into 3 phases of his thinking. The first phase, 1970 - 1980 is the contemplation phase. This phase is more influenced by the thought of taqlîd which is inherited and present in the old Islamic heritage and modern one, as well as a tendency in the Islamic ideology (?Aqîdah) either in the form of kalâm and fiqh schools. The second phase is between the years of 1980 - 1986 is the phase where Shahrûr began to deliver his ideas and his interest into language studies, philosophy and understanding of the Qur?an. The third phase is between the years of 1986 - 1990 which Shahrûr began intensively arranges his thoughts in the topic of Islamic thoughts. In some aspects of his interpretation, He rejected Prophet Muhammad?s asbâb al-nuzûl and it?s temporarily limit, and strengthen the arguments the rejecters of divine revelation as a verse just resting on his asbâb al-nuzûl itself.